FEASIBILITY ANALYSIS FOR HOSPITAL DEVELOPMENT USING COST-BENEFIT APPROACH: A CASE STUDY IN LEGOK DISTRICT, TANGERANG REGENCY - prayogi, budi; Lubis, Vebri (Bina Nusantara University, 2025)
This study evaluates the financial feasibility of hospital development in Legok District, Tangerang Regency, using a cost-benefit approach. The research aims to assess the economic viability of constructing healthcare infrastructure to address the region’s increasing demand for medical services. The findings indicate that the project is financially viable, with a Net Present Value (NPV) of IDR 1.2 billion, an Internal Rate of Return (IRR) of 20.30%, a Payback Period (PP) of 6 years, and a Benefit-Cost Ratio (BCR) of 2. Additionally, qualitative analysis based on stakeholder interviews confirms that the hospital will help meet the growing healthcare needs, particularly for prevalent diseases such as respiratory infections, hypertension, and gastritis. The study underscores the necessity of healthcare infrastructure development in rapidly growing suburban areas with inadequate medical facilities. Despite limitations in financial projections and interview scope, the results affirm the project's feasibility and strategic importance. The study recommends sustained government support, private sector involvement, and further research to ensure long-term sustainability.